Dose-dependent neurotoxicity caused by the addition of perineural dexmedetomidine to ropivacaine for continuous femoral nerve block in rabbits - Wang, Hai-Li (J Int Med Res, 2019)
OBJECTIVE: This study was designed to evaluate the neurotoxicity of dexmedetomidine combined with ropivacaine for continuous femoral nerve block in rabbits. METHODS: Thirty New Zealand rabbits were randomly divided into 5 groups of 6 rabbits each and received a continuous femoral nerve block with saline; 0.25% ropivacaine; or 1, 2, or 3 µg/mL of dexmedetomidine added to 0.25% ropivacaine (Groups A–E, respectively). Sensory and motor function was assessed after the nerve block. The rabbits were anesthetized and killed after 48 hours of a continuous femoral nerve block, and the femoral nerves were removed for light and electron microscopy analyses. RESULTS: The behavior scores were highest in Group A at 2 and 6 hours after injection. The scores were higher in Groups B and C than in Groups D and E at these same time points. All groups showed normal pathological tissues in the femoral nerves under optical microscopy. Under electron microscopy, histological abnormalities were observed only in Group E; none of the other groups exhibited pathological abnormalities. Quantitative analysis of the myelin sheath area revealed no significant difference in the axonal area, total area of the myelin sheath, or ratio of the total axonal area to the total area of the myelin sheath in all groups. CONCLUSION: The lowest doses of dexmedetomidine (1 and 2 µg/mL) combined with 0.25% ropivacaine for continuous femoral nerve block resulted in no neurotoxic lesions, but the higher dose (3 µg/mL) resulted in neurotoxic lesions in this rabbit experimental model.